2011
DOI: 10.4061/2011/494813
|View full text |Cite
|
Sign up to set email alerts
|

Quality Attributes of Cupuaçu Juice in Response to Treatment with Crude Enzyme Extract Produced byAspergillus japonicus586

Abstract: Cupuaçu (Theobroma grandiflorum Schum) is an Amazonian Basin native fruit whose fruit pulp is consumed as a juice which presents high density, viscosity, and turbidity. Pectic enzymes, usually yielded by microorganisms, are used to reduce the juice viscosity and turbidity. The present study aims to evaluate the use of pectic enzymes when processing cupuaçu juice. The cupuaçu juice was obtained by using Aspergillus japonicus 586 crude enzyme extract and incubation at 50°C with agitation (140 rpm) for one hour. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
3
2
0
2
Order By: Relevance
“…Facchini et al [25] reported the same result in their study, where A. japonicus produced a good level of xylanase (31.59 ± 0.17 U/g) on orange bark, which corroborates the results obtained in this work. A similar result was also verified by Teixeira et al [38], who used pectic enzymes to process "Cupuaçu" juice and diminished the amount of waste discharged using a pectinase produced by Aspergillus japonicas during the "Cupuaçu" juice processing. Thus, it was concluded that the extracellular amylase, produced by the thermotolerant A. japonicus, in medium which was supplemented with 1% of the tested carbon sources: starch Merck™, glucose, starch Reagen ®, rice starch, corn starch, maltose, potato starch, orange bark and bagasse has a great potential for the action of enzymes in industries, especially the food industry.…”
Section: Cultivation Of the Fungus A Japonicus In Fiber And Food Resi...supporting
confidence: 76%
“…Facchini et al [25] reported the same result in their study, where A. japonicus produced a good level of xylanase (31.59 ± 0.17 U/g) on orange bark, which corroborates the results obtained in this work. A similar result was also verified by Teixeira et al [38], who used pectic enzymes to process "Cupuaçu" juice and diminished the amount of waste discharged using a pectinase produced by Aspergillus japonicas during the "Cupuaçu" juice processing. Thus, it was concluded that the extracellular amylase, produced by the thermotolerant A. japonicus, in medium which was supplemented with 1% of the tested carbon sources: starch Merck™, glucose, starch Reagen ®, rice starch, corn starch, maltose, potato starch, orange bark and bagasse has a great potential for the action of enzymes in industries, especially the food industry.…”
Section: Cultivation Of the Fungus A Japonicus In Fiber And Food Resi...supporting
confidence: 76%
“…The transformation processes intended to be carried out at industrial level must guarantee high profitability by reducing process costs with high yield. Ma was the most effective method for separating the pulp; however, production costs and high exposure to contamination are a problem for its industrial scaling-up [24]. This method also exposed the pulp to microorganisms affecting the physical and chemical fermentation development in agreement with previous results.…”
Section: Pulping Methodssupporting
confidence: 84%
“…(a)). Similar results have been manifested in grape and cupuacu . Pectin is mainly responsible for turbidity and for causing an increase in viscosity, so pectinase, which hydrolyzes pectin to small, soluble molecules, plays a crucial role in fruit juice production.…”
Section: Resultssupporting
confidence: 73%